农村城镇化与唐山农村经济的跨越式发展 = Rural urbanization and leaping forward of rural economy in Tangshan - 宗玉田 Zong, Yutian (2008)
In order to advance the progress of rural urbanization in Tangshan, we should carry out the strategy in which urbanization, knowledgization, industralization and agricultural modernization develop coordinately.